PENERAPAN GAYA PENYUTRADARAAN HUMANIST DIRECTION DALAM FILM PENDEK DRAMA "KALA MENTARI BERLALU" - Gede Bumi Apnala Bayu; Gede Basuyoga Prabhawita; Putu Raditya Pandet (CALACCITRA: JURNAL FILM DAN TELEVISI, 2026)
This final project report examines the application of the Humanist Direction directing approach in the creation of a short drama film entitled Kala Mentari Berlalu. Kala Mentari Berlalu is inspired by the growing phenomenon of land selling among Balinese communities, which affects not only economic conditions but also cultural values, identity, and emotional attachment to ancestral land. The creative process follows three main stages: pre-production, production, and post-production. The results indicate that the Humanist Direction approach effectively conveys inner character conflicts without excessive dramatization, while clearly delivering a social message about land as cultural heritage, living space, and identity. This film is expected to function as both a reflective medium for audiences and an academic reference for humanist-based film directing practices.